Implementasi Pembelajaran Jarak Jauh (PPJ) dalam Meningkatkan Kemandirian Belajar Siswa - Fathor Rozi; Indria Firdausi Lana (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2021)
This study aims to describe the independence of Distance Learning learning in Madrasah Ibtidiyah students Nurul Iman Sindet Lami Besuk Probolinggo during the Covid-19 pandemic. This research uses a qualitative approach with case studies. The research method used is qualitative through observation, in-depth interviews, and field observations. The results showed that the application of learning using WAG (WhatsApp Group) as an online learning model in madrasah ibtidaiyah has the same steps for each teacher at Madrasah Ibtidaiyah Nurul Iman class VI by utilizing the menu on the WAG (WhatsApp Group), namely: video, voice, discussion, and demonstration. The implication of distance learning in madrasas is the best solution for all teachers in carrying out learning and is very conducive to the Covid-19 pandemic.